CONTEMPORARY FRAMEWORKS FOR FOSTERING ADAPTIVE READINESS AMONG UNDERGRADUATE STUDENTS IN HIGHER EDUCATIONAL ENVIRONMENTS (Multidisciplinary Journal of Science and Technology, 2026)
The transition into higher education represents one of the most cognitively and socially demanding developmental junctures in a learner's academic trajectory. This study examines contemporary frameworks and evidence-based strategies aimed at cultivating adaptive readiness among first-year undergraduate students within rapidly evolving academic ecosystems. Drawing on a convergence of socio-constructivist theory, digital pedagogy, and institutional ecology perspectives, the investigation synthesises global best practices alongside empirical data gathered from four universities in Uzbekistan (n = 420). Findings reveal that integrated support architectures — encompassing mentorship scaffolding, adaptive learning technologies, and proactive wellbeing systems — reduce early attrition risk by up to 2.3-fold and improve first-semester academic performance indices by 31.5 percent compared to conventional enrolment approaches. The paper advances a culturally responsive adaptation model that harmonises Uzbek socio-educational values with twenty-first century pedagogical imperatives, offering transferable implications for post-Soviet and emerging-economy higher education contexts.